State-of-the-Art Review: Technical and Imaging Considerations in Novel Transapical and Port-Access Mitral Valve Chordal Repair for Degenerative Mitral Regurgitation - Hegeman, Romy M. J. J.; Gheorghe, Livia L.; de Kroon, Thomas L.; van Putte, Bart P.; Swaans, Martin J.; Klein, Patrick (Frontiers in Cardiovascular Medicine, 2022)
Degenerative mitral regurgitation (DMR) based on posterior leaflet prolapse is the most frequent type of organic mitral valve disease and has proven to be durably repairable in most cases by chordal repair techniques either by conventional median sternotomy or by less invasive approaches both utilizing extracorporeal circulation and cardioplegic myocardial arrest. Recently, several novel transapical chordal repair techniques specifically targeting the posterior leaflet have been developed as a far less invasive and beating heart (off-pump) alternative to port-access mitral repair. In order to perform a safe and effective minimally invasive mitral chordal repair, thorough knowledge of the anatomy of the mitral valve apparatus and adequate use of multimodality imaging both pre- and intraoperatively are fundamental. In addition, comprehensive understanding of the available novel devices, their delivery systems and the individual procedural steps are required.